Pension Provision of “Special Types of Service” in System of State Apparatus of Russian Empire - D. I. Raskin; Ph. N. Nikitin (Научный диалог)
The issue of the history of pension provision for “special types of service” in the Russian Empire is considered in the article. The provision of pensions for these categories of civil servants is seen as an important part of the government’s policy to stabilize the state apparatus. Attention is paid to the rules for assigning pensions to employees of departments: mining, communications, forestry, customs, court, educational and scientific. The results of a comparative analysis of pensions of these categories of employees with pensions of civil (and in some cases military) employees under the Pension Regulations of 1827 are presented. The privileged position of employees of “special types of services” in relation to other civil and military employees is shown. The question is raised about the history and causes of this privileged position. The novelty of the study is in the fact that for the first time the history of pension provision for special categories of civil servants is considered in a comprehensive manner. It has been proven that the privileged position of these categories of employees was a way to recruit for service in industries that required special qualifications or were distinguished by difficult conditions.